Binary photoacoustic tomography for improved vasculature imaging - Prakash, Jaya (2021)
The proposed binary tomography approach was able to recover the vasculature structures accurately, which could potentially enable the utilization of binary tomography algorithm in scenarios such as therapy monitoring and hemorrhage detection in different organs.